Dednopravne pogodbe in sporazum o odpovedi neuvedenemu dedovanju - Podgoršek, Bojan (Podjetje in delo, 2016)
Our legal system does not allow complete freedom to dispose of property. Disposition of property upon death is limited by the compulsory portion and by the ineffectiveness of the contract of inheritance. These restrictions constitute an obstacle for regulating succession in different life situations. The Constitution leaves to the legislature to determine the manner and the conditions of succession. Legalization of the contract of inheritance would cause greater freedom in disposing of the private property. Before the conclusion of the contract of inheritance would be necessary to ensure complete familiarization with the consequences of the intended transaction. This is the basic function and mission of a notary.
Keywords: dedno pravo; dedovanje; notarji; pogodbe